2016
DOI: 10.2174/1874285801610010045
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based Approaches for the Detection of Clinical Methicillin-resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is an important pathogen that can cause a variety of infections, including superficial and systematic infections, in humans and animals. The persistent emergence of multidrug resistant S. aureus, particularly methicillin-resistant S. aureus, has caused dramatically economic burden and concerns in the public health due to limited options of treatment of MRSA infections. In order to make a correct choice of treatment for physicians and understand the prevalence of MRSA, it is extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 89 publications
0
22
0
1
Order By: Relevance
“…The rplC gene fragment was amplified using A. baumannii rplC specific primers and sequenced. 55,56 The DNA sequencing results were blasted against rplC DNA sequence of A. baumannii in the NIH genetic sequence database. The DNA sequence alignment revealed a C456A single nucleotide mutation, which corresponded to N152K mutation in the protein sequence of RplC (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The rplC gene fragment was amplified using A. baumannii rplC specific primers and sequenced. 55,56 The DNA sequencing results were blasted against rplC DNA sequence of A. baumannii in the NIH genetic sequence database. The DNA sequence alignment revealed a C456A single nucleotide mutation, which corresponded to N152K mutation in the protein sequence of RplC (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…6). Even though, it is well known that femA gene exists in S. aureus and is absent in coagulase negative staphylococcus strains, the gene being successfully considered for detection of MRSA (Oshima et al, 1993;Liu et al, 2016), the results showed in this case that femA gene was not detected in any of the isolates tested.…”
Section: Resultsmentioning
confidence: 80%
“…Methicillin-resistant Staphylococcus aureus (MRSA) has caused many problems in patients due to it multidrug resistance. MRSA strains have been detected since the early 1960s, soon after methicillin became clinically available [1,2]. MRSA continues to increase in the health facilities and it has undergone rapid epidemiological development, spreading outside the boundaries of hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…MRSA continues to increase in the health facilities and it has undergone rapid epidemiological development, spreading outside the boundaries of hospitals. Due to its resistance to multiple antibiotics, new drugs options have been considered to help reduce the morbidity and mortality rates caused by MRSA [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation